UJI KUALITAS MINUMAN KESEHATAN SANTAN KELAPA DAN KECAMBAH KEDELAI (KAJIAN DARI PENGARUH PERBANDINGAN SANTAN KELAPA DENGAN EKSTRAK KECAMBAH KEDELAI DAN LAMA INKUBASI) - Mohammad Su’i; Enny Sumaryati; Frida Dwi Anggraeni; Wijayanti Wijayanti (Universitas Tribhuwana Tunggadewi, 2022)
Coconut milk hydrolyzed using lipase enzymes (endogenous) produces free fatty acids (lauric acid, capric acid, and myristic acid) and monoglycerides that are useful as anti-bacterial and anti-viral. Hydrolysis for 72 hours at 40 oC produced 25.86% lauric acid and 14% monoglycerides from the total oil. Soybean sprouts contain protein, vitamin E, vitamin B, vitamin C, antioxidants, anthocyanins, and isoflavones which are very good for health. Soybean sprouts contain lipase enzymes. If coconut milk mixed with soybean sprout extract is then incubated, the hydrolysis process will be faster so that the amount of free fatty acids produced is higher. This study aimed to study the proportion of coconut milk with soybean sprout extract and incubation time on the quality of health drinks from coconut milk and soybean sprouts. The study used two factors arranged in a factorial manner. The first factor is the ratio of coconut milk with soybean sprout extract 100%: 0%: 75%: 25% and 50: 50%. The second factor is the incubation time (hydrolysis) which is 24, 38, and 72 hours at 40 oC. The results showed that the ratio of coconut milk with soybean sprout extract had no significant effect on levels of free fatty acids, N-amino, taste, color, and aroma. While the incubation time significantly affects free fatty acids, N-amino, taste, and smell. Health drinks from coconut milk and soybean sprout extract with a ratio of 75%: 25% incubation time (hydrolysis) 48 hours is the best treatment with a free fatty acid content of 0.74% N-amino 0.158%, taste score of 4.3 (like), color 3,9 (like) and scent 4 (like).